2018
DOI: 10.1371/journal.pgen.1007359
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical role of the SNARE protein Ykt6 in autophagosome-lysosome fusion

Abstract: The autophagosomal SNARE Syntaxin17 (Syx17) forms a complex with Snap29 and Vamp7/8 to promote autophagosome-lysosome fusion via multiple interactions with the tethering complex HOPS. Here we demonstrate that, unexpectedly, one more SNARE (Ykt6) is also required for autophagosome clearance in Drosophila. We find that loss of Ykt6 leads to large-scale accumulation of autophagosomes that are unable to fuse with lysosomes to form autolysosomes. Of note, loss of Syx5, the partner of Ykt6 in ER-Golgi trafficking do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 68 publications
3
83
1
1
Order By: Relevance
“…Recent studies have uncovered the yeast SNARE, Ykt6, as important in autophagosome-vacuole/lysosome fusion in yeast (Bas et al, 2018;Gao et al, 2018), and that mammalian Ykt6 ortholog (Matsui et al, 2018;Takats et al, 2018) plays a potentially dominant (over Stx17) role in mammalian autophagosome-lysosome fusion. Whereas the exact mechanism of Ykt6 in maturation has not been agreed upon, with differences in proposed models (Matsui et al, 2018;Takats et al, 2018), it is worth noting that Ykt6 is also part of one of the retrograde trafficking routes from endosomes to TGN that includes GOS-28/ GOSR1 (Tai et al, 2004), an mAtg8-binding SNARE as discussed above. Nevertheless, our data here suggest that Stx17 still plays a very important role in autophagosomal flux, revealed in the requirement for a STX16/STX17 double KO to block autophagic flux using the conventional and well-accepted LC3 flux assay (Klionsky et al, 2016), and reflected in autophagic degradation of a diverse panel of substrates: mitochondria, peroxisomes, M. tuberculosis, and ribosomes.…”
Section: B Validation Of Stx16/stx17 Dko By Western Blot Analysis In mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have uncovered the yeast SNARE, Ykt6, as important in autophagosome-vacuole/lysosome fusion in yeast (Bas et al, 2018;Gao et al, 2018), and that mammalian Ykt6 ortholog (Matsui et al, 2018;Takats et al, 2018) plays a potentially dominant (over Stx17) role in mammalian autophagosome-lysosome fusion. Whereas the exact mechanism of Ykt6 in maturation has not been agreed upon, with differences in proposed models (Matsui et al, 2018;Takats et al, 2018), it is worth noting that Ykt6 is also part of one of the retrograde trafficking routes from endosomes to TGN that includes GOS-28/ GOSR1 (Tai et al, 2004), an mAtg8-binding SNARE as discussed above. Nevertheless, our data here suggest that Stx17 still plays a very important role in autophagosomal flux, revealed in the requirement for a STX16/STX17 double KO to block autophagic flux using the conventional and well-accepted LC3 flux assay (Klionsky et al, 2016), and reflected in autophagic degradation of a diverse panel of substrates: mitochondria, peroxisomes, M. tuberculosis, and ribosomes.…”
Section: B Validation Of Stx16/stx17 Dko By Western Blot Analysis In mentioning
confidence: 99%
“…In the context of autophagy, SNAREs have been studied at different stages along the autophagy pathway (Nair et al, 2011;Itakura et al, 2012;Moreau et al, 2013;Kimura et al, 2017). Recent studies have indicated that additional SNAREs may be required or even be dominant in this process (Matsui et al, 2018;Takats et al, 2018). Recent studies have indicated that additional SNAREs may be required or even be dominant in this process (Matsui et al, 2018;Takats et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ykt6 has been recently shown to be implicated in two cognate SNARE complexes in autophagosomal/lysosomal fusion (Matsui et al, 2018; Takats et al, 2018). One complex consists of Stx7 (Qa SNARE localized in the lysosome) and SNAP29 (Qbc SNARE) (Matsui et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its roles in the secretory and endocytic pathways, Ykt6 has recently been implicated in macroautophagy (hereafter referred to as autophagy) (Gao, Reggiori, & Ungermann, 2018) (Bas et al, 2018) (Takats et al, 2018) (Matsui et al, 2018). Autophagy is a highly conserved intracellular degradation pathway of long-lived proteins, misfolded proteins, and damaged organelles (Mizushima & Komatsu, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation